Nongenomic Thyroxine Regulation of Voltage-gated Sodium Current During Embryonic Development - Yonkers, Marc A.; Ribera, Angeles B. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2011)
Thyroid hormones modulate ion flux across cellular membranes by effects on both transporters and channels. One such mechanism involves modulation of voltage-gated sodium current in spinal neurons by thyroxine. Experiments in zebrafish embryos have shown that thyroxine rapidly upregulates the current amplitude of a specific sodium channel subtype, nav1.6a. In mammals, the orthologous channel, Nav1.6, is expressed at nodes of Ranvier. In contrast to traditional thyroid hormone mechanisms that depend on nuclear receptors and regulation of gene expression, the regulation of nav1.6a channels involves a plasma membrane receptor, the integrin dimer αVβ3, indicative of a nongenomic mechanism. Although acute changes in thyroxine levels lead to rapid changes in nav1.6a function in vivo, the concentration of thyroxine in vivo is relatively stable in the absence of experimental intervention. On this basis, the endogenous concentration of thyroxine provides on-going regulation of voltage-gated sodium channel function through interaction with integrin αVβ3. This interaction is evident with blockade of the thyroxine-αVβ3 pathway, via antagonists of thyroid hormone (tetrac) or the integrin receptor (LM609 antibody). These interventions also produce significant changes in biologically relevant zebrafish behavior. In summary, thyroxine binding to integrin αVβ3 regulates voltage-gated sodium current in the embryonic nervous system and serves as an important mechanism by which thyroid hormones influence development and behavior.
Keywords: nongenomic